Bio-based gas-responsive food packaging: From dynamic microenvironment regulation to real-time freshness monitoring - Ruiting Tao; Chenrui Ouyang; Jiangbo Wang; Yuhang Ye; Shaohua Jiang; Xiaoshuai Han (Trends in Food Science & Technology, 2026)

Study on the degradation of tetracycline in aqueous solution using MIL-53(Fe) generated by needle–plate pulsed discharge - Ruiting Jian; Manli He; Jiushan Cheng; Bowen Liu; Zhengduo Wang; Zhongwei Liu (Journal of Environmental Chemical Engineering, 2026)

Can unmanned aerial vehicle laser scanning serve as an effective alternative to traditional field methods for predicting tree growth in even-aged Chinese fir (Cunninghamia lanceolata) plantations? - Rui Li; Baoying Wang; Ruiting Liang; Zhidan Ding; Zhaoting Zhu; Yujun Sun (European Journal of Forest Research, 2026)

Endoplasmic reticulum stress-mediated glycophagy drives macrophage M1 polarization in silica nanoparticles-induced pulmonary fibrosis - Lei Bao; Zihan Geng; Linpeng Niu; Lili Shi; Liyi He; Yaxian Pang; Cunhui Zhang; Yan Liu; Jiawei Chen; Beibei Shi; Ruiting Wu; Jingyuan Wang; et al. (Journal of Environmental Sciences, 2026)

Seed-associated Pseudomonas enhance the growth of Ambrosia trifida - Xue Chen; Chunying Li; Chang Wang; Jieyu Yang; Ruiting Ju; Fengjuan Zhang; Jihua Wu (Plant and Soil, 2026)

Efficient degradation vs. enhanced persistence: How soil nutrients drive divergent pesticide fates via microbial strategies on the Tibetan plateau - Ruiting Dong; Meiqi Jiang; Dan Yang; Jie Li; Ruigang Wang; Liping Weng; Yang Sun (Environmental Research, 2026)

Chemical distance outweighs phylogeny in VOC-mediated cross-species plant defense communication - Chaonan Wang; Danfeng Liu; Xiao Xu; Mingjun Gao; Jiawei Wang; Jieren Jin; Yupeng Geng; Ruiting Ju; Yi Wang; Xiaoming Lu; Jihua Wu; Bo Li (Science China Life Sciences, 2026)

Pan-cancer characterization of the pyrimidine catabolic enzyme UPB1 identifies a tumor-suppressive prognostic biomarker in skin cutaneous melanoma - Yingli Men; Yi Shao; Yongfeng Chen; Ping Wang; Yiyang Li; Zhenzhen Yang; Ruiting Feng; Hui Wang; Yinsen Song; Cong Ding (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Haplotype-resolved long-read sequencing reveals parent-of-origin effects of tandem-repeat variation in autism spectrum disorder - Jinchen Li; Tengfei Luo; Xue Ren; Songyu Yang; Hui Quan; Yan Zhu; Senwei Tan; Xiangbin Jia; Pei Yu; Yuanfeng Huang; Zhaowei Jiang; Xudong Xiang; et al. (Science Bulletin, 2026)

Optimization of Agrobacterium-mediated transformation of commercial heirloom tomato cultivars to develop novel traits via CRISPR/Cas9 genome editing - Jordan Oxendine; Elsa Ibarra-Reyes; Junchi Ma; Carrie Li; Sarah Baron; Allison E. Hwang; Ruiting Wang; Daniel Rodriguez-Leal (Planta, 2026)
Main conclusion Trait development for commercial heirloom tomatoes can be advanced by optimization of tissue culture and transformation via Agrobacterium and CRISPR/Cas9 mutagenesis. Abstract Genetic improvement using new genome editing approaches relies on the efficient delivery of the CRISPR/Cas system in the vegetable crop tomato. Previous protocols for tomato transformation have primarily focused on a handful of cultivars (M82, Ailsa Craig, Microtom, Sweet-100) with very little commercial relevance, and it is not clear if these protocols can be implemented directly in other commercially relevant varieties. Heirloom tomatoes are sought for their deep and diverse flavor but have not been subjected to systematic crop improvement via conventional breeding or biotechnology approaches such as transgenesis or genome editing. Therefore, we tested the transformation and regeneration capacity of six different heirloom cultivars known for their superior taste and market relevance in the US. Subsequently, we optimized rooting conditions and used the GRF4-GIF1 chimeric developmental regulator to successfully recover transgenic plants. Finally, we evaluated the efficiency of targeted genetic modification using the CRISPR/Cas9 genome editing system in several of these cultivars. We demonstrate that our optimizations led to successful transformation of several heirloom varieties, including the generation of edited plants for target genes modifying plant architecture and flowering time. Our results set the foundation for a biotechnology platform to deliver improved traits to local and regional heirloom varieties using genome editing.

Corrigendum to “Development of active sustainable films based on phytic acid and silicate/polyvinyl alcohol hybrid system for wrapping chicken meat” [Food Packaging and Shelf Life 54 (2026) 101720] - Chaoqun Li; Fanyu Meng; Yongyan Yang; Jingfei Wang; Ruiting Zhang; Chongruihan Li; Yue Wang; Jia Wang; Yan Gao; Shuangling Zhong; Xuejun Cui (Food Packaging and Shelf Life, 2026)

Spatiotemporal dynamics and drivers of water and carbon use efficiency in the Yellow River basin with harmonized MODIS and GLASS data - Shilun Zhou; Ruiting Lyu; Feiyang Wang; Xiaodan Guan; Ning Nie (Journal of Hydrology, 2026)

Climate-driven dynamics of surface water temperature and its coupled responses to lake heatwaves and cyanobacterial blooms in Lake Taihu - Lei Sun; Ruiting Xu; Yakun Feng; Haozhang Dai; Menglin Yuan; Chenhui Wu; Hao Wang; Ya Liu; Cuiling Jiang (Journal of Environmental Management, 2026)

Exploring factors influencing the height growth of Cunninghamia lanceolata based on bootstrap bayesian network and random forest - Baoying Wang; Rui Li; Yujun Sun; Ruiting Liang; Zhaoting Zhu (Trees, 2026)

The role of easily biodegradable organic materials as soil biostimulants in mediating the rapid enhancement of soil aggregate stability - Zheng MA; Xinlei ZHANG; Yujian WANG; Luyao YANG; Ruiting GUO; Longtao TU; Zhenlun LI (Pedosphere, 2026)

Development of active sustainable films based on phytic acid and silicate/polyvinyl alcohol hybrid system for wrapping chicken meat - Chaoqun Li; Fanyu Meng; Yongyan Yang; Jingfei Wang; Ruiting Zhang; Chongruihan Li; Yue Wang; Jia Wang; Yan Gao; Shuangling Zhong; Xuejun Cui (Food Packaging and Shelf Life, 2026)

Short-Chain Fatty Acids Mitigate Perinatal Methylmercury-Induced Cognitive Impairment Via Modulation of the Gut Microbiota Composition - Binqian Han; FangRen Li; Qin Lu; Ruiting Ran; Lianrui Li; Weiying An; Fang Chen; Wenjuan Wang (Biological Trace Element Research, 2026)

Leveraging commuting patterns and workplace charging to advance equitable EV charger access - Ruiting Wang; Ha-Kyung Kwon; Katherine H. Jordan; Scott J. Moura; Madhur Boloor; Michael L. Machala (Transportation Research Part D: Transport and Environment, 2026)

Astrocytic HMGCR-Mediated Cholesterol Alleviated Parkinson’s Disease Phenotypes by Inhibiting NF-κB Neuroinflammation - Xiaofeng Tian; Qing Liu; Jiacheng Zhang; Huijiao Du; Zhaoran Wei; Linjie Sun; Jiamin Gao; Ruiting Zhao; Lei Wang; Yizhou Zhang (Molecular Neurobiology, 2026)

Construction of built-in electric field in Ru/Vo-NiCo2O4 heterostructure for efficient ethylene glycol oxidation reaction coupled nitrate to ammonia electrolysis - Jingwen Ma; Ruiting Wang; Jinhao Liu; Ying Tian; Junbin Li (Journal of Environmental Chemical Engineering, 2025)

Surface oxygen coverage-mediated *OOH modulation enables highly selective H2O2 electrosynthesis - Jinchao Xu; Wanying Wang; Yuang Shi; Huan Li; Tengyao Sun; Xiang Wan; Chunning Zhao; Ruiting Hao; Weichao Wang (Chemical Engineering Journal, 2025)

The interaction between Ir nanocrystallites and Ni2P nanosheets regulates the adsorption energetics of intermediates for boosting ethanol electrolysis - Xiaoyu Zhang; Ruiting Chen; Ge Ma; Xin Wang; Yu Chen; Zhongwei Chen (Chemical Engineering Journal, 2025)

Effects of mixing with Masson pine on the growth and drought resilience of Chinese fir in subtropical forests - Ruiting Liang; Yifu Wang; Zhidan Ding; Yujun Sun; Siyu Qiu (European Journal of Forest Research, 2025)

Revealing the nano-empowered fluorescent sensor arrays for the food safety point-of-care testing: An overview of mechanism and applications - Yaodong Guo; Xiaowen Zhang; Ruiting Wang; Jianlong Wang (Trends in Food Science & Technology, 2025)

Carbon black induced pulmonary fibrosis through piR-713551/PIWIL4 targeting THBS2 signal pathway - Mengruo Wang; Yong Niu; Qingping Liu; Peihao Yang; Mengqi Wu; Ruiting Wu; Beibei Shi; Jiawei Chen; Jingyuan Wang; Zhe Du; Yaxian Pang; Lei Bao; et al. (Journal of Environmental Sciences, 2025)

Integrating photo-Fenton-like Fe3O4/CdS-O modules into sponge-based gel solar evaporator for synergistic water regeneration and pollutant degradation - Xuyao Qiao; Shuguang Ning; Hongyao Zhao; Ruiting Ni; Wanyu Zhang; Yangping Zhang; Linzhi Zhai; Danhong Shang; Yanyun Wang; Tongyi Yang; Mengnan Wang; Fu Yang (Journal of Environmental Chemical Engineering, 2025)

Enabling kinetics matching in electrocatalytic ammonia synthesis by leveraging spatially-confined Cu/Fe2O3 heterointerfaces to maximize *H supply and utilization - Mengting Liu; Fu Yang; Hongyao Zhao; Xiu Zhong; Ruiting Ni; Kwame Nana Opoku; Zhenxiao Wang; Yangping Zhang; Yanyun Wang; Feng Zeng; Yinlong Zhu; Weidong Shi (Chemical Engineering Journal, 2025)

Oligo-residual disease in metastatic ALK-positive NSCLC treated with alectinib - Xi Yang; Xiao Chu; Ruiting Ye; Jianjiao Ni; Ya Zeng; Yue Zhou; Qing Xia; Shengping Wang; Qiao Li; Shuai Liu; Zhengfei Zhu; Li Chu (Clinical & Experimental Metastasis, 2025)

A six - stage evaluation model for optimizing urban EV charging and swapping station locations - Jianming Cai; Yanzi Xiao; Yaxin Wang; Ruiting Cai (Sustainable Cities and Society, 2025)

Neoproterozoic tectonic evolution of the northwestern Yangtze Block: Constraints from the Bijigou intermediate-acid magmatism in the Hannan massif - Yan Luan; Yunxiu Ren; Ruiting Wang; Xiaohui Sun (Acta Geochimica, 2025)

Reliability assessment of using different heavy metals in remote sedimentary records to reconstruct historical pollution - Jiapeng Gao; Ruiting Song; Xinrui Wang; Kexin Wan; Jianle Zhang; Guanqi Shan; Dejun Wan; Shaogang Wang (Environmental Pollution, 2025)

Three-dimensional ordered macroporous nitrogen-doped carbon for efficient adsorption of flavonoids from plant extraction - Chuanmao Li; Wenyuan Lyu; Ruiting Lin; Haoran Liu; Yingfei Wang; Datong Chen; Fengliang Wang; Yingwei Li (Chemical Engineering Journal, 2025)

Electron-deficient asymmetric Co centers marry oxygen vacancy for NO3RR: Excellent activity and anion resistance property - Hao Lu; Kwame Nana Opoku; Zhenxiao Wang; Ruiting Ni; Mengting Liu; Yanyun Wang; Yangping Zhang; Chao Yu; Aihua Yuan; Fu Yang; Weidong Shi (Chemical Engineering Journal, 2025)

Cropland Exposure to Extreme Dryness and Wetness in China Under Shared Socioeconomic Pathways - Ruiting Yang; Guojie Wang; Yunxia Zhang; Peng Zhang; Shijie Li; Pedro Cabral (International Journal of Climatology, 2025)
Global warming by human activities have exacerbated the occurrence of extreme climatic events, which have taken a huge toll on human production and livelihoods. Predicting future changes in extreme wetness and dryness, along with the extent of cropland exposure to these conditions under various scenarios, is essential for effective climate adaptation and achieving sustainable development goals. This study employs the Standardised Antecedent Precipitation Evapotranspiration Index (SAPEI) method to identify extreme dryness and extreme wetness in China for future projections (2021–2100), and to analyse the characteristics of changes in the pixel‐day, intensity, and affected area by extreme dryness and wetness, as well as the cropland exposures to them under different shared socioeconomic pathways (SSPs). We find that the intensity and spatial extent of extreme dryness and wetness significantly increase in future climate projections, especially under high‐emission scenario compared to low‐emission scenario. Under the scenarios with increased emissions, the cropland exposure increased in most parts of China. Therefore, it is particularly urgent to keep the low‐emission scenario in order to minimise the cropland damage caused by extreme drought and wetness in China in the future.

Gut microbiota modulation by L-Fucose as a strategy to alleviate Ochratoxin A toxicity on primordial follicle formation - Ruiting Wang; Jie Song; Muyu Cai; Yuan Xue; Jing Liu; Ning Zuo; Massimo De Felici; Junjie Wang; Wei Shen; Xiaofeng Sun (Journal of Hazardous Materials, 2024)

Room temperature oxygenated groups addition in carbon materials via ozone oxidation for boosting electrochemical H2O2 production - Jinchao Xu; Wanying Wang; Yuang Shi; Huan Li; Ruiting Hao; Gang Chen; Wen Wang; Chunning Zhao; Weichao Wang (Chemical Engineering Journal, 2024)

Effect of Unfermented Soy Product Consumption on Blood Lipids in Postmenopausal Women: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Jiahe Qi; Ruiting Zhu; Jing Mao; Xi Wang; Haiyan Xu; Lirong Guo (Journal of the Academy of Nutrition and Dietetics, 2024)

Polymer tethering strategy modified ZIF67 derived cobalt-confined nanocage for norfloxacin degradation: Tailored reactive sites and beneficial local microenvironment - Hongyao Zhao; Enxian Yuan; Kwame Nana Opoku; Mengting Liu; Xiu Zhong; Ruiting Ni; Zhenxiao Wang; Yanyun Wang; Zengjing Guo; Chongchen Wang; Fu Yang (Chemical Engineering Journal, 2024)

Effectiveness of thinning in mitigating post-drought legacy effects on Chinese fir in subtropical plantation forests, Southeastern China - Ruiting Liang; Yifu Wang; Yujun Sun; Zhaoting zhu; Rui Li (Dendrochronologia, 2024)

Layered deposited MoS2 nanosheets on acorn leaf like CdS as an efficient anti-photocorrosion photocatalyst for hydrogen production - Yao Wang; Tengyang Gao; Ruiting Li; Yan Chen; Wen Luo; Yang Wu; Yu Xie; Yong Wang; Yifan Zhang (Fuel, 2024)

Associations of environmental cadmium exposure with kidney damage: Exploring mediating DNA methylation sites in Chinese adults - Yuan Wei; Xiaochen Wang; Qi Sun; Wanying Shi; Wenli Zhang; Xu Gao; Yawei Li; Ruiting Hao; Xiaojie Dong; Chen Chen; Kangning Cao; Weilong Jiang; et al. (Environmental Research, 2024)

Instance segmentation and stand-scale forest mapping based on UAV images derived RGB and CHM - Yunhong Xie; Yifu Wang; Zhao Sun; Ruiting Liang; Zhidan Ding; Baoying Wang; Shaodong Huang; Yujun Sun (Computers and Electronics in Agriculture, 2024)

Transcriptome and small RNA analysis unveils novel insights into the C4 gene regulation in sugarcane - Xiuting Hua; Zhen Li; Meijie Dou; Yanqing Zhang; Dongxu Zhao; Huihong Shi; Yihan Li; Shuangyu Li; Yumin Huang; Yiying Qi; Baiyu Wang; Qiyun Wang; et al. (Planta, 2024)

Correlation analysis and predicting modeling of pyrolysis gas based on landfill excavated waste pyrolysis characteristics - Yufeng Du; Ruiting Liu; Ping Han; Jin Wang; Feiyong Chen; Guanzhong Chen (Chemosphere, 2024)

Corrigendum to “Horizontal transfer of antibiotic resistance genes within the bacterial communities in aquacultural environment” [Sci. Total Environ. 820 (2022) 153286] - Songzhe Fu; Qingyao Wang; Rui Wang; Yixiang Zhang; Ruiting Lan; Fenglan He; Qian Yang (Science of The Total Environment, 2024)

Expedite extraction of Pb2+ from low-strength wastewater in the half-wave rectified alternating current electrochemical method by accelerating lead electrodeposition kinetics - Tongtong Yue; Ruiting Wang; Yutong Zhong; Benzheng Li; Shuang Lv; Wei Feng (Journal of Cleaner Production, 2024)

Transcriptome Analysis Revealed Potential Immune-Related Genes of Head Kidney in the Yellow Catfish (Pelteobagrus fulvidraco) Challenged with Aeromonas hydrophila - Senhao Jiang; Yuting Lei; Ti Wang; Ruiting Ma; Chunqiang Hou; Qiuning Liu (Fishes, 2024)
Yellow catfish (Pelteobagrus fulvidraco) is an important freshwater fish species in aquaculture. However, as intensive farming has rapidly expanded, infectious diseases caused by various bacteria, such as Aeromonas hydrophila, have also increased. We conducted a transcriptomic analysis of head kidney from P. fulvidraco stimulated by A. hydrophila strain SHOU. A total of 43,249 unigenes with an average length of 1342 bp were obtained following assembly and annotation. By analyzing GO and KEGG enrichment, many differentially expressed genes (DEGs) and pathways related to immunity were identified. Out of the 973 DEGs that were identified, 553 were upregulated and 420 were downregulated. Moreover, KEGG enrichment analysis revealed that the innate immune system, including the TNF signaling pathway, NF-kappa B signaling pathway, and the Toll-like receptor signaling pathway involved in the defense, is activated against infectious response. Real-time quantitative reverse transcription-PCR (qRT-PCR) analysis demonstrated that immune response genes were upregulated in response to A. hydrophila stimulation compared to the control. In conclusion, this study provides valuable insights into the immune defense mechanism of P. fulvidraco and sheds light on the host immune genes involved in the response to bacterial infection.

Global meta-analysis and three-year field experiment shows that deep placement of fertilizer can enhance crop productivity and decrease gaseous nitrogen losses - Peng Wu; Qi Wu; Hua Huang; Lin Xie; Haoyuan An; Xintong Zhao; Fangtao Wang; Ziting Gao; Ruiting Zhang; Kemoh Bangura; Jianfu Xue; Min Sun; et al. (Field Crops Research, 2024)

Effects of Chaihu Shugan San on Brain Functional Network Connectivity in the Hippocampus of a Perimenopausal Depression Rat Model - Ruiting Huang; Min Gong; Xue Tan; Jianying Shen; You Wu; Xiaoshi Cai; Suying Wang; Li Min; Lin Gong; Wenna Liang (Molecular Neurobiology, 2024)

Individual and interactive effects of air warming and elevated O3 on carbon fixation and allocation in two urban tree species - Yijing Wang; Sheng Xu; Bo Li; Yan Li; Ruiting Wang; Wei Chen; Xingyuan He; Felicity Hayes; Maihe Li (Agricultural and Forest Meteorology, 2024)

Permeability–Friction Relationships for Propped Fractures in Shale - Jiayi Yu; Jiehao Wang; Yan Li; Amr El-Fayoumi; Ruiting Wu; Xiaolong Liu; Peggy Rijken; Andrew P. Rathbun; Derek Elsworth (Rock Mechanics and Rock Engineering, 2023)

Temporal changes in size inequality and stand growth partitioning between tree sizes under various thinning intensities in subtropical Cunninghamia lanceolata plantations - Ruiting Liang; Yunhong Xie; Yujun Sun; Baoying Wang; Zhidan Ding (Forest Ecology and Management, 2023)

Relative effects of climate, stand environment and tree characteristics on annual tree growth in subtropical Cunninghamia lanceolata forests - Ruiting Liang; Yujun Sun; Siyu Qiu; Baoying Wang; Yunhong Xie (Agricultural and Forest Meteorology, 2023)

Molecular Identification and Expression Analysis of an Intelectin Gene in the Yellow Catfish Pelteobagrus fulvidraco (Siluriformes: Bagridae) - Senhao Jiang; Yuting Lei; Yanxuan Li; Wanyan Sun; Ti Wang; Ruiting Ma; Qiuning Liu; Boping Tang (Fishes, 2023)
Intelectins (ITLNs) are a family of calcium-dependent lectins with carbohydrate-binding capacity, are distributed across various vertebrates, and play an important role in the innate immune response against pathogen infection. The yellow catfish Pelteobagrus fulvidraco (Siluriformes: Bagridae) is an economically important fish in China. The aim of this study was to quantify the gene expression of ITLN in response to pathogen-associated molecular patterns (PAMPs) stimulation. Here, the ITLN gene of P. fulvidraco was characterized and named PfITLN. The full-length cDNA of PfITLN was 1132 bp, including a 5’-untranslated region (UTR) of 140 bp, a 3’-UTR of 110 bp, and an open reading frame (ORF) of 882 bp encoding a polypeptide of 293 amino acids, which contains a signal peptide and two fibrinogen-related domains (FReDs). PfITLN had a molecular weight of 32.39 kDa with a theoretical pI of 5.03. The deduced PfITLN amino acid sequence had 81%, 64%, and 55% homology with Ictalurus furcatus, Danio rerio, and Homo sapiens, respectively. Moreover, the predicted tertiary protein structure of PfITLN was highly similar to that of other animals, and phylogenetic analysis showed that the PfITLN protein was close to those of other Teleostei. Real-time quantitative reverse transcription-PCR (qRT-PCR) analysis showed PfITLN expression in all examined tissues, with the highest abundance seen in the liver, followed by the head kidney, spleen, trunk kidney, and muscle. After PAMP infection with lipopolysaccharide (LPS) and polyriboinosinic polyribocytidylic acid (poly I:C), the expression levels of PfITLN were significantly upregulated at different time points. These results suggested that PfITLN might be involved in innate immunity.

The role of total antioxidant capacity and malondialdehyde of seminal plasma in the association between air pollution and sperm quality - Lipeng Li; Tengfei Feng; Ruiting Wu; Yaling Zhang; Ning Wang; Mengqi Wu; Yaxian Pang; Sujuan Yang; Aimin Yang; Dengsuo Zhang; Guimin Hao; Rong Zhang (Environmental Pollution, 2023)

Performance analysis of two-stage CO2 transcritical refrigeration cycles with absorption subcooling and mechanical recooling - Caoxuheng Huang; Zeyu Li; Zhihao Ye; Ruiting Wang (International Journal of Refrigeration, 2023)

Chitosan-based mussel-inspired hydrogel for rapid self-healing and high adhesion of tissue adhesion and wound dressings - Yongyan Yang; Ying Ma; Jingfei Wang; Liru You; Ruiting Zhang; Qingye Meng; Shuangling Zhong; Wenqi He; Xuejun Cui (Carbohydrate Polymers, 2023)

Association between meteorological factors and COVID-19 transmission in low- and middle-income countries: A time-stratified case-crossover study - Yu Wang; Yiran Lyu; Shilu Tong; Cheng Ding; Lan Wei; Mengying Zhai; Kaiqiang Xu; Ruiting Hao; Xiaochen Wang; Na Li; Yueyun Luo; Yonghong Li; et al. (Environmental Research, 2023)

Maternal tamoxifen exposure leads to abnormal primordial follicle assembly - Jinxin Zhao; Jiaona Zhang; Yonghong Sun; Ruiting Wang; Dachuan Shi; Wei Shen; Xiaofeng Sun (Histochemistry and Cell Biology, 2023)

Rapid and sensitive detection of methyl parathion in rice based on carbon quantum dots nano-fluorescence probe and inner filter effect - Ruiting Zhang; Liyuan Zhang; Runzhong Yu; Changyuan Wang (Food Chemistry, 2023)

High adhesion hydrogel electrolytes enhanced by multifunctional group polymer enable high performance of flexible zinc-air batteries in wide temperature range - Zhihao Shang; Hang Zhang; Mengfei Qu; Ruiting Wang; Li Wan; Da Lei; Zhengzheng Li (Chemical Engineering Journal, 2023)

Effect of Oat Consumption on Blood Pressure: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Huihui Xi; Wei Zhou; Yirou Niu; Ruiting Zhu; Saikun Wang; Yingze Guo; Wenqing Liu; Xuance Xiong; Lirong Guo (Journal of the Academy of Nutrition and Dietetics, 2023)

Linear charging-discharging of an ultralong UVA persistent phosphor for advanced optical data storage and wide-wavelength-range detector - Chuanlong Wang; Yahong Jin; Jiaxin Zhang; Xiangguang Li; Haoyi Wu; Ruiting Zhang; Qing Yao; Yihua Hu (Chemical Engineering Journal, 2023)

Moderate physical activity against effects of short-term PM2.5 exposure on BP via myokines-induced inflammation - Mengqi Wu; Yaxian Pang; Meiyu Chen; Lipeng Li; Lina Yan; Jie Ning; Qingping Liu; Yaling Zhang; Tao Jiang; Aijuan Kang; Xiaoyan Huang; Wentao Hu; et al. (Science of The Total Environment, 2023)

Fine-mapping and candidate gene analysis of qFL-c10-1 controlling fiber length in upland cotton (Gossypium hirsutum L.) - Ruiting Zhang; Chao Shen; De Zhu; Yu Le; Nian Wang; Yuanxue Li; Xianlong Zhang; Zhongxu Lin (Theoretical and Applied Genetics, 2022)

Comparative analysis of machine learning algorithms and statistical models for predicting crown width of Larix olgensis - Siyu Qiu; Ruiting Liang; Yifu Wang; Mi Luo; Yujun Sun (Earth Science Informatics, 2022)

Nebulization Therapy with Umbilical Cord Mesenchymal Stem Cell-Derived Exosomes for COVID-19 Pneumonia - Meiping Chu; Hao Wang; Linjie Bian; Jiehui Huang; Danping Wu; Ruiting Zhang; Fangli Fei; Yigang Chen; Jiazeng Xia (Stem Cell Reviews and Reports, 2022)
Background Scientists have been facing numerous challenges in the development of an effective therapeutic strategy for the treatment of COVID-19 pneumonia. Several studies have suggested that improving patient immunity and reducing lung injury induced by SARS-CoV-2 may be effective for treating patients with COVID-19. Methods A pilot trial of nebulization therapy with exosomes of mesenchymal stem cells (MSCs) was performed on seven patients with COVID-19 pneumonia. Exosomes secreted from MSCs were collected and purified using multiple ultrafiltration steps. All patients were treated with nebulization of MSC-derived exosomes, and primary safety and efficacy outcomes were evaluated. Results Our clinical study demonstrated that nebulization of MSC-derived exosomes is a novel method that might be utilized in the treatment of COVID-19 pneumonia. Nebulization of MSC-derived exosomes did not induce acute allergic or secondary allergic reactions but did promote the absorption of pulmonary lesions and reduce the duration of hospitalization for mild cases of COVID-19 pneumonia. Conclusions Nebulization of MSC-derived exosomes is a safe, effective, and simple method, and their application at the beginning of treatment may be more beneficial. Trial Registration Chinese Clinical Trial Registry, ChiCTR2000030261. Registered on 26 February 2020. Graphical Abstract

White Matter Free Water is a Composite Marker of Cerebral Small Vessel Degeneration - Peiyu Huang; Ruiting Zhang; Yeerfan Jiaerken; Shuyue Wang; Hui Hong; Wenke Yu; Chunfeng Lian; Kaicheng Li; Qingze Zeng; Xiao Luo; Xinfeng Yu; Xiao Wu; et al. (Translational Stroke Research, 2022)

Semi-synthetic product dihydroartemisinin inhibited fibronectin-1 and integrin-β1 and interfered with the migration of HCCLM6 cells via PI3K-AKT pathway - Ruiting Wu; Yan Gao; Jiaqin Wu; Chunli Wang; Li Yang (Biotechnology Letters, 2020)

The assessment of different vegetation indices for spatial disaggregating of thermal imagery over the humid agricultural region - Kai Liu; Shudong Wang; Xueke Li; Yao Li; Bo Zhang; Ruiting Zhai (International Journal of Remote Sensing, 2020)

An experiment to improve the capability of the regional climate model RegCM4.5 to simulate the land surface climate in dense vegetation areas - Minghao Yang; Ruiting Zuo; Liqiong Wang; Fengliang Hu; Chao Wang; Wei Ge (Journal of Earth System Science, 2019)

Fuzzy comprehensive evaluation of the disaster reduction ability of an ethnic minority accumulation area based on an analytic hierarchy process - Xiaoxiao Wang; Ruiting Shi; Yuting Lu; Ying Zhou (Environmental and Ecological Statistics, 2019)

Hydrophobin HFBII-4 from Trichoderma asperellum induces antifungal resistance in poplar - Huifang Zhang; Shida Ji; Ruiting Guo; Chang Zhou; Yucheng Wang; Haijuan Fan; Zhihua Liu (Brazilian Journal of Microbiology, 2019)

ALIX increases protein content and protective function of iPSC-derived exosomes - Ruiting Sun; Yingying Liu; Meng Lu; Qianqian Ding; Pingping Wang; Heng Zhang; Xiaoyu Tian; Peng Lu; Dan Meng; Ning Sun; Meng Xiang; Sifeng Chen (Journal of Molecular Medicine, 2019)

Characterization of the complete chloroplast genome sequence of Cardamine macrophylla (Brassicaceae) - Ting Ren; Yanci Yang; Jiao Wang; Ruiting Zhang; Zhan-Lin Liu (Conservation Genetics Resources, 2018)

Complete chloroplast genome sequence of Pedicularis cheilanthifolia, an alpine plant in China - Ruiting Zhang; Jiao Wang; Kai Han; Ting Ren; Shuyun Zeng; Edward Biffin; Zhan-Lin Liu (Conservation Genetics Resources, 2017)

Characterization of the complete chloroplast genome of the Cortusa matthioli subsp. pekinensis (Primulaceae) - Jiao Wang; Ruiting Zhang; Ting Ren; Kai Han; Shuyun Zeng; Edward Biffin; Zhan-Lin Liu (Conservation Genetics Resources, 2017)

Origin of the Lengshuigou porphyry–skarn Cu deposit in the Zha-Shan district, South Qinling, central China, and implications for differences between porphyry Cu and Mo deposits - Guiqing Xie; Jingwen Mao; Ruiting Wang; Deming Meng; Jia Sun; Junzhi Dai; Tao Ren; Jianbi Li; Haijie Zhao (Mineralium Deposita, 2017)

A one-step ligation system for rapid generation of armed, conditionally-replicating adenoviruses - Xing Li; Ruiting Xia; Jing Zhao; Dongyang Wang; Qinwen Mao; Haibin Xia (Biotechnology Letters, 2013)

Equilibrium mechanism analysis on the physical processes of IAP3.0 - Zuo Ruiting; Wang Liqiong; Zeng Qingcun; Zhang Ming (Advances in Atmospheric Sciences, 2005)